Genius: a very short introduction - "Robinson, Andrew" (New York, 2011)
Genius is the name we give to a quality of work that transcends fashion, celebrity, fame, and reputation. Somehow, genius abolishes both the time and the place of its origin. Shakespeare's plays and Mozart's melodies and harmonies continue to move people in languages and cultures far removed from their native England and Austria. Similarly, Darwin's ideas are still required reading for every working biologist; they continue to generate fresh thinking and experiments around the world. The first concise study of genius in both the arts and the sciences, this Very Short Introduction uses the life and work of familiar geniuses--including Homer, Leonardo, Tolstoy, Marie Curie, Galileo, and Newton--to illuminate both the individual and the general aspects of genius. In particular, Robinson explores the roles of talent, heredity, parenting, education, training, hard work, intelligence, personality, mental illness, inspiration, eureka moments, and luck, in the making of genius.
Keywords: Genius